Índices de política de concorrência: avaliação do caso brasileiro - Falco, Guilherme de Aguiar (Universidade Federal de São Carlos, 2014)
Market regulation brings on the expectation that government's intervention improves the economy. For example, the assumption that competitive environments enable efficient allocation of resources influences the development of antitrust policies and encourages free competition. The promotion of competition through laws and regulatory agencies follows this reading and public antitrust policies are disseminated throughout developed and developing countries. However, despite its wide application, these regulations lack empirical mechanisms that organize their major institutional properties and allow proper assessment of policy operation and its effects over the economy. This master thesis replicates to the Brazilian reality a set of indexes - previously developed for 13 other jurisdictions - that seek to translate institutional and qualitative information into objective, quantitative and comparable cross-country information. The indexes are created upon the compilation and classification of the characteristics of a particular jurisdiction with respect to a benchmark of best practices in deterring anticompetitive conducts. The immediate goal is to review and critique different designs of competition policy agencies and statutes, allowing cross-time and cross country analysis. The results for the Brazilian policy are positive regarding institutional features (rules of the game), both in cross-time and cross-country perspectives; Brazil presents inferior results regarding enforcement (human/financial resources and volume of cases analyzed by the competent agency); the aggregate index presents high levels in a cross-country analysis.
Competition policy indexes: assessment of the brazilian case
Keywords: concorrência; direito antitruste; Conselho Administrativo de Defesa Econômica (Brasil); regulação econômica; política de concorrência; dissuasão de práticas anticompetitivas, índices de política da concorrência; CADE; economic regulation; competition policy and antitrust; deterrence of anticompetitive practices, competition policy indexes; CADE; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::ORGANIZACAO INDUSTRIAL E ESTUDOS INDUSTRIAIS